2016
DOI: 10.1007/s00705-016-3019-0
|View full text |Cite
|
Sign up to set email alerts
|

A real-time RT-PCR for rapid detection and quantification of mosquito-borne alphaviruses

Abstract: Mosquito-borne alphaviruses are widely distributed throughout the world, causing important human illnesses. Therefore, the development of methods to enable early diagnosis of infections by alphavirus is essential. We show here the development and evaluation of a quantitative real-time RT-PCR using genus-specific primers to the nsP1 viral gene of all mosquito-borne alphaviruses. The specificity and sensitivity of the assay were tested using seven alphaviruses and RNA transcribed from Venezuelan equine encephali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
(55 reference statements)
0
7
0
1
Order By: Relevance
“…Over the past 40 years, various molecular assays have been developed for the detection of VEEV and VEE complex viruses [5,[11][12][13][14][15][16][17][18]25]. Many involve conventional or nested RT-PCRs that employ pan-alphavirus primers to amplify a large region of the genome, with subsequent species differentiation using specific nested primers, biotinylated probes, sequencing, or melt-curve analysis [11][12][13][14][15][16][17]. Vina-Rodriguez et al, reported an rRT-PCR that was designed from an alignment of 33 VEEV sequences [18].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Over the past 40 years, various molecular assays have been developed for the detection of VEEV and VEE complex viruses [5,[11][12][13][14][15][16][17][18]25]. Many involve conventional or nested RT-PCRs that employ pan-alphavirus primers to amplify a large region of the genome, with subsequent species differentiation using specific nested primers, biotinylated probes, sequencing, or melt-curve analysis [11][12][13][14][15][16][17]. Vina-Rodriguez et al, reported an rRT-PCR that was designed from an alignment of 33 VEEV sequences [18].…”
Section: Discussionmentioning
confidence: 99%
“…The VEEV complex, MADV and EEEV viruses have been detected throughout the Americas and may account for a significant proportion of non-dengue acute febrile illness (2, 3, 5, 9). Although several assays have been developed for the molecular detection of VEEV subtypes and VEEV complex (14-20), many are laborious and time-consuming based in multiple PCR rounds or posterior genome sequencing that can be only implemented in laboratories with appropriate facilities (14)(15)(16)(17)(18)(19)(20). Co-circulation and the potential for co-infection with these viruses further complicates their detection, particularly when they present similar clinical presentations and there is a lack of available and convenient methods for detection of VEEV complex viruses and MADV (19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…of Mayaro, and highlight the need for a comprehensive look, such as the One Health vision, for a better management of this threat in the country. O gene codificante da proteína não estrutural 1 (nsP1), é uma região do genoma bem conservada entre os Alfavírus, e por esta razão tem sido alvo de estudos para o diagnóstico de alfaviroses, bem como a identificação de Alfavírus ainda desconhecidos (ROMEIRO, M. F. et al, 2016).…”
Section: Discussionunclassified